Particle size effect in the mechanically assisted synthesis of β-cyclodextrin mesitylene sulfonate - Menuel, Stéphane; Saitzek, Sébastien; Monflier, Eric; Hapiot, Frédéric (Beilstein Journal of Organic Chemistry, 2020)
The mechanically assisted synthesis of organic compounds has recently focused considerable attention as it may be unique in features to selectively direct the reaction pathway. In the continuation of our work on the synthesis of modified cyclodextrins (CDs) via mechanochemical activation, we sought to discriminate the contribution of supramolecular effects and grinding during the course of a reaction in the solid state. As such, we recently investigated the influence of the particle size of β-CD in the synthesis of β-CD mesitylene sulfonate (β-CDMts) in the solid state using a vibrating ball-mill. We were particularly interested in the role of the particle size on the kinetics of the reaction. In this study, we show that grinding β-CD reduces the particles size over time down to a limit of 167 nm. The granulometric composition remains rather invariant for grinding times over 1 h. Each type of β-CD particles reacted with mesitylenesulfonyl chloride (MtsCl) to produce β-CDMts. Contrary to what could be intuitively anticipated, smaller particles did not lead to the highest conversions. The impact of grinding on the conversion was limited. Interestingly, the proportion of β-CDMts mono-substituted on the primary face significantly increased over time when the reaction was carried out in the presence of KOH as a base. The data series were confronted with kinetics models to get insight in the way the reactions proceeded. The diversity of possible models suggests that multiple mechanochemical processes can account for the formation of β-CDMts in the solid state. Throughout the study, we found that the reactivity depended more upon diffusion phenomena in the crystalline parts of the material than on the increase in the surface area of the CD particles resulting from grinding.
Keywords: beta-cyclodextrin; chemoselectivity; grinding; mechanosynthesis; reactivity

(untitled) - Andersen, J.; Mack, J. (Green Chem., 2018)

(untitled) - Tan, D.; Friščić, T. (Eur. J. Org. Chem., 2018)

(untitled) - Achar, T. K.; Bose, A.; Mal, P. (Beilstein J. Org. Chem., 2017)

(untitled) - Friščić, T.; Halasz, I.; Beldon, P. J.; Belenguer, A. M.; Adams, F.; Kimber, S. A. J.; Honkimäki, V.; Dinnebier, R. E. (Nat. Chem., 2013)

(untitled) - Cravotto, G.; Caporaso, M.; Jicsinszky, L.; Martina, K. (Beilstein J. Org. Chem., 2016)

(untitled) - Jicsinszky, L.; Calsolaro, F.; Martina, K.; Bucciol, F.; Manzoli, M.; Cravotto, G. (Beilstein J. Org. Chem., 2019)

(untitled) - Wen, H.; Jung, H.; Li, X. (AAPS J., 2015)

(untitled) - Kurkov, S. V.; Loftsson, T. (Int. J. Pharm., 2013)

(untitled) - Jansook, P.; Ogawa, N.; Loftsson, T. (Int. J. Pharm., 2018)

(untitled) - Popielec, A.; Loftsson, T. (Int. J. Pharm., 2017)

(untitled) - Jug, M.; Mura, P. A. (Pharmaceutics, 2018)

(untitled) - Cugovčan, M.; Jablan, J.; Lovrić, J.; Cinčić, D.; Galić, N.; Jug, M. (J. Pharm. Biomed. Anal., 2017)

(untitled) - Brusnikina, M.; Silyukov, O.; Chislov, M.; Volkova, T.; Proshin, A.; Mazur, A.; Tolstoy, P.; Terekhova, I. (J. Therm. Anal. Calorim., 2017)

(untitled) - Menuel, S.; Doumert, B.; Saitzek, S.; Ponchel, A.; Delevoye, L.; Monflier, E.; Hapiot, F. (J. Org. Chem., 2015)

(untitled) - Oliva, E.; Mathiron, D.; Rigaud, S.; Monflier, E.; Sevin, E.; Bricout, H.; Tilloy, S.; Gosselet, F.; Fenart, L.; Bonnet, V.; Pilard, S.; Djedaini-Pilard, F. (Biomolecules, 2020)

(untitled) - Menuel, S.; Léger, B.; Addad, A.; Monflier, E.; Hapiot, F. (Green Chem., 2016)

(untitled) - Cousin, K.; Menuel, S.; Monflier, E.; Hapiot, F. (Angew. Chem., Int. Ed., 2017)

(untitled) - Murakami, T.; Harata, K.; Morimoto, S. (Tetrahedron Lett., 1987)

(untitled) - Fujita, K.; Ishizu, T.; Obe, K.-i.; Minamiura, N.; Yamamoto, T. (J. Org. Chem., 1992)

(untitled) - Yamamura, H.; Iida, D.; Araki, S.; Kobayashi, K.; Katakai, R.; Kano, K.; Kawai, M. (J. Chem. Soc., Perkin Trans. 1, 1999)

Image Processing with ImageJ - Pascau, J.; Mateos Perez, J. M. (Packt Publishing Ltd., 2013)

(untitled) - Colombo, I.; Grassi, G.; Grassi, M. (J. Pharm. Sci., 2009)

(untitled) - Hutchings, B. P.; Crawford, D. E.; Gao, L.; Hu, P.; James, S. L. (Angew. Chem., Int. Ed., 2017)

(untitled) - Weng, H.-L.; Parrott, E. L. (J. Pharm. Sci., 1984)

(untitled) - Galwey, A. K.; Brown, M. E. (Proc. R. Soc. London, Ser. A, 1995)

(untitled) - Takacs, L. (Prog. Mater. Sci., 2002)

(untitled) - Štrukil, V.; Fábián, L.; Reid, D. G.; Duer, M. J.; Jackson, G. J.; Eckert-Maksić, M.; Friščić, T. (Chem. Commun., 2010)

(untitled) - Khan, A. R.; Forgo, P.; Stine, K. J.; D'Souza, V. T. (Chem. Rev., 1998)

(untitled) - Sforza, S.; Galaverna, G.; Corradini, R.; Dossena, A.; Marchelli, R. (J. Am. Soc. Mass Spectrom., 2003)

(untitled) - Khawam, A.; Flanagan, D. R. (J. Phys. Chem. B, 2006)

(untitled) - Schneider, C. A.; Rasband, W. S.; Eliceiri, K. W. (Nat. Methods, 2012)